Hanif Kureishi - Moore-Gilbert, B. J. 1952- (Contemporary world writers, 2001)
"Hanif Kureishi's work, in a range of genres, from drama to film, fiction and short stories, has elicited widespread critical acclaim and - at times - provoked sharp condemnation. Kureishi has explored a number of the key social and cultural issus of recent years, including the legacies of colonialism, "multi-culturalism", changing conceptions of gender and sexuality, globalization and relations between popular culture and the canon. In this comprehensive study of Kureishi's work Bart Moore-Gilbert provides a detailed account of his work to date, from Kureishi's early involvement in "fringe" theatre to the short story collections. Moore-Gilbert locates Kureishi's work securely in its historical, social, cultural and critical contexts, as well as providing detailed readings of all the major works."--BOOK JACKET.